2021
DOI: 10.1002/cpz1.332
|View full text |Cite
|
Sign up to set email alerts
|

Guinea Pig and Mouse Models for Genital Herpes Infection

Abstract: This article describes procedures for two preclinical animal models for genital herpes infection. The guinea pig model shares many features of genital herpes in humans, including a natural route of inoculation, self‐limiting primary vulvovaginitis, spontaneous recurrences, symptomatic and subclinical shedding of HSV‐2, and latent infection of the associated sensory ganglia (lumbosacral dorsal root ganglia, DRG). Many humoral and cytokine responses to HSV‐2 infection in the guinea pig have been characterized; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The anti-HSV-2 effects of PSSD were further tested in an HSV-2-induced murine genital herpes model [ 21 ]. As shown in Figure 5 a,b, the mice body weight of the virus control group continuously reduced and sharply decreased after day 7 p.i.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-HSV-2 effects of PSSD were further tested in an HSV-2-induced murine genital herpes model [ 21 ]. As shown in Figure 5 a,b, the mice body weight of the virus control group continuously reduced and sharply decreased after day 7 p.i.…”
Section: Resultsmentioning
confidence: 99%
“…The HSV-2-induced murine genital herpes model has been established and used for studying the anti-HSV-2 effects of PSSD in vivo [ 21 ]. Herein, we found that vaginal gel treatment of PSSD significantly reduced the symptoms of genital herpes and inhibited HSV multiplication in the reproductive tract of mice.…”
Section: Discussionmentioning
confidence: 99%
“…Female guinea pigs were infected intravaginally with 2 × 10 5 plaque-forming units of HSV-2 strain MS that had been passaged in a cell culture to attenuate lethality [ 21 ]. Animals were randomized into equal groups based on the number of days with genital lesions for the first 14 days post-infection.…”
Section: Methodsmentioning
confidence: 99%
“…S-540956 acts as a potent cancer vaccine adjuvant by targeting draining lymph nodes [ 20 ]. We assessed the potency of S-540956 as a component of a therapeutic vaccine for genital herpes using a guinea pig genital herpes model [ 21 , 22 ]. We administered S-540956 with HSV-2 gD2 subunit protein to guinea pigs previously infected intravaginally with HSV-2, and evaluated the recurrent genital lesions and vaginal shedding of HSV-2 DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Guinea pig pathology was monitored daily and scored as follows; 0, no redness/disease; 1, redness and/or swelling; 2, a few small vesicles; 3, several large vesicles; 4, several large ulcers with skin breakages. At stage 4, guinea pigs were euthanised as a humane endpoint [12].…”
Section: Hsv-2 Pathologymentioning
confidence: 99%